Nachhaltige Energieversorgung in Entwicklungsländern: Zur Rolle der Weltbank in Mosambik - Lucius Mayer-Tasch (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
– In the debate about a global transformation of energy systems, technology transfer and financial aid are seen as crucial factors for the promotion of sustainable energy in de-veloping countries. As the single most important aid agency, the World Bank claims to fight both energy poverty and climate change in its partner countries. This paper ana-lyzes the World Bank's involvement in the Mozambican energy sector by applying en-vironmental, social and economic criteria for sustainable development. The analysis is based on interviews conducted with World Bank staff, Mozambican officials, represen-tatives of bilateral donor organisations, NGO activists, and energy experts. It focuses on completed and on-going World Bank projects in Mozambique's electricity, coal and gas sectors. The study shows that the World Bank's involvement in each sector has both positive and negative impacts. While the World Bank claims to have stopped funding new coal development projects, it is still promoting the large-scale resumption of coal production by a private investor. It is also promoting a radical reform of the Mozambican electricity sector that might produce a decrease in energy access, especially in rural areas. At the same time the Bank is advancing the off-grid use of renewable energy and the im-provement of access to electricity in peri-urban areas. By facilitating the export of natu-ral gas to Mozambique's highly coal-dependent neighbouring country South Africa, it contributes to the reduction of greenhouse gas emissions in that country. The gas ex-ports will generate considerable additional revenues for the Mozambican government. The future quality of governance in Mozambique will determine whether these revenues will be used for poverty alleviation or not. The case study further shows that the World Bank increasingly respects its safeguard policies in specific investment projects and integrates environmental concerns in its sector projects. At the same time it seems to keep on missing its mandate to alleviate poverty by over-emphasising liberal market reforms. Since the World Bank is both promoting fossil fuel projects and renewable energy (with GEF funds) it does not con-sistently incorporate climate change concerns in its energy policy choices.
Keywords: 300; Umweltverträgliche Energiepolitik; Energieversorgung; Nachhaltige Entwicklung; Entwicklungsprojekt; Entwicklungshilfe; Mosambik; Entwicklungsländer